Conservation or Change for Works of the Modern Movement - Dunnett, James (Docomomo Journal, 2018)
The Modern Movement in architecture, in so far as any such movement can be defined, was predicated on the idea that architecture had to change to reflect the radical technological advances that had occurred during the century preceding its formulation, and also to reflect the changing social needs that those advances had generated. Architecture, it was felt, had ossified and lost vitality as a result of not recognizing those changes. A century has now passed since the Modern Movement first formulated this program, and technical advances and the social changes they induce have of course by no means ceased, rather they have accelerated. So, it seems legitimate to say that a technologically – and socially – determined architecture should reflect these further advances and changes. The evolution continues. But does that mean that each Modern Movement building created at a particular point in that evolution has in itself to continue to change in order to “catch up” with the evolution subsequent to its creation? It is a question that has importance when it comes to considering the conservation of Modern Movement architecture. It is an assertion that would ignore the formal element in architecture.